Cognitive Barriers in Learning English as a Second Language at Tertiary Level: A Survey of English as a Second Language Class at the University of Jaffna - Sarmatha, S. (Department of Linguistics, University of Kelaniya, Sri Lanka, 2016)
This paper aims to prob the principal difficulties and barriers of the second language learners in the ESL classroom at tertiary level. this study mainly focuses on the barriers of learning English as a second language at the University of Jaffna and to provide some effective teaching approaches to improve English knowledge of undergraduates. The researcher has conducted this survey to explore the cognitive barriers in the skill of writing in English. this study has been carried out in relation to the second-year students in the Faculty of Arts, University of Jaffna. The objective of this study is to examine the cognitive barriers in the ESL classroom. the researcher tries to investigate what are the causes for the difficulties and the link between the barriers and the language learners’ family factors, cultural factors and psychological traits. this study also provides valuable suggestions to improve the learners’ language acquisition level and the development of writing skills, how to motivate them via effective teaching approaches and strategies and help them to overcome their learning barriers. The data has been analyzed through qualitative and quantitative research methods. this study is based on writing materials that were collected from the undergraduates to gather information and discussion regarding this study. this study helps to diagnose the learners’ cognitive barriers in writing, to bring an effective learning outcome and to improve the learners’ cognitive level in the ESL classroom.
Keywords: Cognitive barriers; ESL classroom; Language acquisition; Second language learning; Writing skills